2014
DOI: 10.1155/2014/597275
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cane: Its Concept, Development, Characteristics, and Prospects

Abstract: Unlike conventional sugar cane (Saccharum spp.) energy cane is a cane selected to have more fiber than sucrose in its composition. This is obtained simply by altering the genetic contribution of the ancestral species of sugarcane using traditional breeding methods. The resulting key feature is a significant increase in biomass yield. This happens because accumulating sugar is not physiologically a simple process and results in penalty in the side of fiber and yield. This review paper describes the initial conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
1
24

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 65 publications
4
118
1
24
Order By: Relevance
“…In between those extremes, all distinct sucrose and fiber tradeoff is presented by a segregant population of a cross between ancestors (RAMDOYAL & BADALOO, 2007;WANG et al, 2008;SANTCHURN et al, 2012). Type I energy cane can be exploited by conventional sugar cane distilleries to produce first generation ethanol (EG1) from its juice, along with steam and electric power from the bagasse (ALEXANDER, 1985;RAO et al, 2007;MATSUOKA et al, 2014). For industries other than ethanol-producing plants, which are interested only in the bagasse to feed boilers, the energy cane juice remains as a side-product with high value as a fermentable broth, even higher than the bagasse per se.…”
Section: Resumo: O Principal Interesse Na Cana Energia Reside Na Prodmentioning
confidence: 99%
See 1 more Smart Citation
“…In between those extremes, all distinct sucrose and fiber tradeoff is presented by a segregant population of a cross between ancestors (RAMDOYAL & BADALOO, 2007;WANG et al, 2008;SANTCHURN et al, 2012). Type I energy cane can be exploited by conventional sugar cane distilleries to produce first generation ethanol (EG1) from its juice, along with steam and electric power from the bagasse (ALEXANDER, 1985;RAO et al, 2007;MATSUOKA et al, 2014). For industries other than ethanol-producing plants, which are interested only in the bagasse to feed boilers, the energy cane juice remains as a side-product with high value as a fermentable broth, even higher than the bagasse per se.…”
Section: Resumo: O Principal Interesse Na Cana Energia Reside Na Prodmentioning
confidence: 99%
“…Energy cane appears as a valuable alternative de cana-de-açúcar feedstock for bioenergy, at least for tropical countries (ALEXANDER, 1985;MATSUOKA et al, 2014). Botanically, the fundamental distinguishing characteristic of energy cane in comparison with conventional sugarcane is its genomic constitution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, small sugar production increases of approximately 1 to 1.5% per year have been obtained. The average yield of sugarcane in Brazil, the world's largest sugarcane producer, is approximately 74 t ha -1 ; however, the theoretical production potential is approximately 400 t ha -1 (Dal-Bianco et al, 2012;Matsuoka et al, 2014;Waclawovsky et al, 2010). Waclawovsky et al (2010) showed that, in Brazil, the commercial maximum yield (large land areas) was 260 t ha -1 and an experimental maximum (individual trials on smaller land areas) was 299 t ha -1 .…”
Section: Mixed Modeling Of Yield Components and Brown Rust Resistancementioning
confidence: 99%
“…Currently most of the developed nations rely on fossil fuel sources for energy, which are non-renewable, limited in supply and convert the fossilized carbon reserves into carbon di oxide, which acts as a greenhouse gas, responsible for global warming. But the future energy sources have to be sustainable and renewable, costeffective and efficient, safe and easy to harvest (McKendry, 2002;Chum and Overend, 2001). The first sign of an alternate and more sustainable source of energy dates back to 1970s, when America faced the first fossil oil crisis, which resulted in a spike in oil prices that led to the first push for the development of renewable energy (Karp and Halford, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass is the most common form of renewable resource that is abundantly used in the developing nations but not so much in the industrially developed nations (McKendry, 2002). According to the current estimate, biofuel and wastes supply 10.2% (or 50 EJ) of th anniversary of the discovery of Hatch-Slack pathway, more popularly known as the C 4 photosynthetic pathway in sugarcane leaves.…”
Section: Introductionmentioning
confidence: 99%